Free Convection Boundary Layer Flow Over Cylinders of Elliptic Cross Section with Constant Surface Heat Flux - Ahmad, Syakila; Md Arifin, Norihan; Mohd Nazar, Roslinda; Pop, Ioan (European Journals, Inc., 2008)
The steady laminar free convection boundary layer flow over horizontal cylinders of elliptic cross section when the major axis is both horizontal (blunt elliptic cylinder) and vertical (slender elliptic cylinder) subjected to a constant surface heat flux placed in an incompressible viscous fluid is considered in this paper. The governing boundary layer equations are solved numerically using the Keller box method. The numerical solutions are obtained for various values of the Prandtl number and parameter b/a (the ratio of the major and minor axes of the cylinder) for both blunt and slender orientations.